Answer:
x=2
Step-by-step explanation:
logx (2x)^3 = 6
We can rewrite without the exponent
3 logx (2x) = 6
Divide by 3
3/3 logx (2x) = 6/3
logx (2x) = 2
Raise each side to the base x
x^ logx (2x) =x^ 2
2x = x^2
Subtract 2x from each side
2x-2x = x^2 -2x
0 = x^2 -2x
Factor an x
0 = x(x-2)
Using the zero product property
x =0 x-2 =0
x =0 x=2
We cannot have a base of 0, so x cannot equal 0
x=2
Answer: See explanation
Step-by-step explanation:
You didn't give the options relating to the question.
To solve this first, you need to know that we have to note that (+) × (-) = (-). Therefore, 1.25+(-0.75) will be thesame as writing 1.25 - 0.75. This will then be:
= 1.25 - 0.75
= 0.50
1: y=8, (-2,8)
2: y=6, (-1,6)
3: y=0, (2,0)
Step-by-step explanation:
Insert the x value into each equation then see what value of y that you need to get 4 on the right hand side of the equation.
Answer:
210.65 ft
round as needed
Step-by-step explanation:
Law of Cosines
c^2 = a^2 + b^2 - 2abCosC
c^2 = 125^2 + 210^2 - 2(125)(210)Cos73
c^2 = 15,625 + 44,100 - 15349.5
c^2 = 44,375.5
c = 210.654931107724132